An artificial SEI film-coated negative electrode material and its preparation method and application

By constructing an artificial SEI film on the negative electrode material of lithium-ion batteries, using CMC-Li, carbon dioxide and hydrogen fluoride to form dense inorganic lithium salt components, the first Coulomb efficiency and cycle life problems of graphite-based carbon-based materials in lithium-ion batteries were solved. Efficient battery performance improvement and cost control are achieved.

CN119133418BActive Publication Date: 2025-01-17XINGTAI RISUN NEW ENERGY TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411586280.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-11-08
Publication Date
2025-01-17
Estimated Expiration
2044-11-08

AI Technical Summary

Technical Problem

The first Coulomb efficiency and cycle life problems of graphite carbon-based materials in lithium-ion batteries are mainly due to the fragility and instability of SEI films, resulting in rapid attenuation of battery capacity, and existing modification technologies such as carbon coating and conductive polymers There are problems with high cost and limited effect.

Method used

Carboxymethylcellulose lithium (CMC-Li) is used as the organic lithium salt component of the artificial SEI film. By introducing carbon dioxide and hydrogen fluoride, a dense inorganic lithium salt component is formed to construct a uniform artificial SEI film, which is packaged through spray drying technology. Covering the surface of the negative electrode material, improving the battery's first charge and discharge efficiency and cycling performance.

Benefits of technology

It significantly improves the first charge and discharge efficiency and reversible capacity of the negative electrode material, improves the rate fast charging and cycling performance, reduces the battery impedance, extends the battery cycle life, and reduces the preparation cost.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119133418B_ABST
    Figure CN119133418B_ABST
Patent Text Reader

Abstract

The present invention relates to the technical field of battery negative electrode materials, and specifically discloses an artificial SEI film-coated negative electrode material and a preparation method and application thereof. The artificial SEI film-coated negative electrode material comprises a negative electrode material matrix and an artificial SEI film coated on the surface of the negative electrode material matrix; the raw material of the artificial SEI film is an artificial SEI film glue, and the preparation method of the artificial SEI film glue comprises the following steps: carbon dioxide and hydrogen fluoride are introduced into hydroxymethyl cellulose lithium glue until the pH of the system is 5.5-7.0, so as to obtain an artificial SEI film glue. The present invention uses CMC-Li as the organic lithium salt component of the artificial SEI membrane, and introduces a dense inorganic lithium salt component by introducing CO2 and HF. The composition of the artificial SEI membrane is similar to that of the natural SEI membrane, which significantly improves the first effect and reversible capacity of the negative electrode material, improves the rate fast charging performance and cycle performance, and has high commercial value.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of battery negative electrode materials, and in particular to an artificial SEI film-coated negative electrode material and a preparation method and application thereof. Background Art

[0002] Lithium-ion batteries have the characteristics of high energy density, long cycle life, and low cost, and play a leading role in energy storage. Graphite has the characteristics of moderate cost, suitable charge and discharge potential, high electronic conductivity and ionic conductivity, low expansion rate, low temperature and high temperature, and good cycle performance. It is the main component of lithium-ion battery negative electrode materials. The theoretical gram capacity of graphite is 372mAh / g, but the actual discharge capacity is only 335mAh / g~364mAh / g, and because the active lithium is consumed and activated to form SEI (Solid Electrolyte Interphase) membrane, the first coulomb efficiency (first efficiency) of graphite is only 90%~95% (button lithium-ion battery), and the first efficiency in the full battery is only 88%~92%, which makes the energy density of electrode materials and batteries smaller; the compatibility between graphite carbon negative electrode materials and solvents is poor, which will also lead to faster cycle decay. The first efficiency and cycle life issues have become the biggest barriers to the use of graphite carbon-based materials.

[0003] At present, in order to solve the problems of poor initial Coulomb efficiency and poor cycle performance of graphite negative electrode materials, the modification method of graphite negative electrode materials is generally carbon coating modification. The carbon materials used for coating include asphalt, resin materials, etc. Coating a layer of amorphous carbon on the surface of graphite will increase the overall interlayer spacing of the negative electrode material, thereby facilitating Li + Diffusion inside it. Modification technologies such as surface treatment and element doping have also achieved certain results. For example, by using metal and its oxide materials for coating, through the composite of graphite and metal and its oxide, the coating material can introduce its own conductivity into the graphite negative electrode, effectively reducing the charge transfer resistance and improving the Li +The diffusion coefficient of the graphite material is increased, thereby inhibiting the decomposition of the electrolyte on the graphite surface, improving the electrochemical properties of the graphite material, and preventing the reaction between the electrolyte and graphite to a certain extent, reducing the irreversible capacity of the material, and improving the charge and discharge efficiency. In addition, conductive polymers are also one of the commonly used surface coating materials for negative electrode materials, such as polythiophene, polypyrrole, polyaniline, etc. The conductive polymer coating can effectively cover the active points on the surface of the graphite material, reduce the irreversible capacity loss of the electrode, and provide a good conductive network to ensure good conductivity between graphite particles. However, amorphous carbon coating technology will lead to a decrease in the first efficiency of graphite negative electrode materials, poor high-temperature performance of the material, and the high-temperature carbonization step greatly increases the cost. The coating process of metals and their oxides is complicated, and the manufacturing cost and raw material cost are both high, and the improvement effect on the first charge and discharge efficiency and cycle stability is limited. The conductive polymer coating technology has limited improvement effect on the low first efficiency caused by the consumption of lithium in SEI film formation, and the cost performance is low.

[0004] The SEI film is a thin film formed in lithium-ion batteries and is located on the surface of the negative electrode material of lithium batteries. During the initial charging process of lithium-ion batteries, the SEI film is composed of electrolyte decomposition products and electrode material reduction products. It has a close relationship with the initial efficiency and electrochemical performance of lithium-ion batteries. The SEI film has the following functions: ① Enhance the stability of battery performance: The SEI film can prevent direct contact between the solvent and salt in the electrolyte and the electrode material, thereby reducing the decomposition of the electrolyte and the corrosion of the electrode material, which helps to maintain the stable performance of the battery; ② Enhance the cycle stability and charge and discharge efficiency of the battery: The SEI film can promote the Li + conduction and reduce Li + ③ Prevent battery short circuit: SEI film, as an isolation layer, can prevent direct contact between electrode materials and reduce the risk of short circuit inside the battery. However, the natural SEI film is very fragile and unstable. When the volume of the negative electrode material changes continuously during the process of lithium insertion and extraction, the SEI film will continue to rupture and regenerate. The newly generated SEI film will continue to accumulate, forming a thick passivation layer on the electrode surface. In the continuous decomposition and reconstruction, a large amount of active lithium and electrolyte will be consumed, which will eventually cause the rapid attenuation of battery capacity, reduce the coulombic efficiency of the battery, and shorten the cycle life.

[0005] Constructing an artificial SEI film is one of the most effective methods to improve the ionic conductivity of the surface SEI and inhibit the growth of dendrites on lithium metal anodes. Although the inorganic artificial SEI layer has good electrochemical stability, high mechanical modulus and more effective lithium ion diffusion pathways, it is easy to break when the volume of lithium metal changes greatly, resulting in failure of the lithium anode. Therefore, constructing a homogeneous, consistent and ideal artificial SEI film is an urgent problem to be solved in this field. Summary of the invention

[0006] In view of the above problems, the present invention provides an artificial SEI film-coated negative electrode material, a preparation method and application thereof. The present invention uses highly dispersible carboxymethyl cellulose lithium (CMC-Li) as the organic lithium salt component of the artificial SEI film, introduces a dense inorganic lithium salt component by introducing carbon dioxide and hydrogen fluoride, and utilizes the artificial SEI film to significantly improve the first effect and reversible capacity of the negative electrode material, improve the fast-rate charging performance and cycle performance, and at the same time, the reaction process is mild and the cost is low.

[0007] In order to solve the above technical problems, the technical solution provided by the present invention is:

[0008] In a first aspect, the present invention provides an artificial SEI film-coated negative electrode material, comprising a negative electrode material substrate and an artificial SEI film coated on the surface of the negative electrode material substrate;

[0009] The raw material of the artificial SEI film is an artificial SEI film glue, and the preparation method of the artificial SEI film glue comprises the following steps:

[0010] Carbon dioxide and hydrogen fluoride are introduced into the carboxymethyl cellulose lithium colloid until the pH of the system is 5.5-7.0 to obtain an artificial SEI membrane colloid.

[0011] Compared with the prior art, the artificial SEI membrane coated negative electrode material provided by the present invention uses CMC-Li as the organic lithium salt component of the artificial SEI membrane, and introduces a dense inorganic lithium salt component by introducing carbon dioxide and hydrogen fluoride. The artificial SEI membrane contains both organic components and inorganic components, which are similar to the composition of the natural SEI membrane. CMC-Li has high dispersibility, which fully guarantees the uniformity of the coating and the easy dispersion and processability of the coated product. The present invention uses an artificial SEI membrane (glue) to modify the surface of the negative electrode material matrix. The artificial SEI membrane (glue) of a specific component is cross-linked on the surface of the negative electrode material matrix to form a dense and uniform polymer layer, which effectively prevents the formation of lithium dendrites and improves the safety performance of the battery cell; the artificial SEI membrane has high toughness and can effectively improve the damage caused by Li + The side reaction caused by the volume change of the negative electrode material caused by embedding or unembedding improves the cycle performance of the battery; the artificial SEI film also has a high Li + The migration rate can significantly optimize the fast charging ability of the negative electrode material and reduce the impedance of the battery; through the uniform coating modification of the artificial SEI film, the consumption of active lithium in the negative electrode material during the first charge and discharge process is greatly reduced, which greatly improves the reversible capacity of the negative electrode material.

[0012] The present invention uses CO2 and HF gas to neutralize the pH value of the CMC-Li glue system, and simultaneously introduces inorganic components in the SEI membrane to obtain an artificial SEI membrane glue in one step. The main components of the artificial SEI membrane include an organic layer and a non-base layer. The organic layer has a loose and porous structure. + The main components include ROLi, RCOOLi, ROCOLi, RCOO2Li and ROCO2Li (R represents the organic chemical group in carboxymethyl cellulose); the inorganic layer structure is dense, Li + It is permeable, and its main components are Li2O, LiOH, LiF and Li2CO3, etc. The present invention adopts a one-step method to prepare the artificial SEI membrane glue, and the equipment and operation are simple, and it has high commercial value.

[0013] Preferably, the mass ratio of the artificial SEI membrane glue to the negative electrode material matrix is ​​(0.5-10):100, and more preferably (1-8):100.

[0014] The present invention can further ensure that the battery has the best comprehensive performance by limiting the above mass ratio.

[0015] Preferably, the molar ratio of the carbon dioxide to the hydrogen fluoride is 0.8:1 to 1.2:1.

[0016] The present invention can control the content of the corresponding inorganic lithium salt in the artificial SEI membrane glue by limiting the above-mentioned usage.

[0017] Preferably, the negative electrode material matrix is ​​selected from at least one of artificial graphite, natural graphite, hard carbon, soft carbon, silicon carbon or silicon oxygen.

[0018] The artificial SEI film-coated negative electrode material provided by the present invention has a wide range of applications and is applicable to almost all negative electrode materials, especially carbon-based negative electrode materials.

[0019] Preferably, the method for preparing the carboxymethyl cellulose lithium colloid comprises the following steps:

[0020] S1, mixing sodium carboxymethyl cellulose with water to obtain sodium carboxymethyl cellulose glue;

[0021] S2, adding an inorganic acid solution to the sodium carboxymethyl cellulose glue solution, and performing an acidification reaction at 40° C. to 50° C. to obtain a carboxymethyl cellulose acid glue solution;

[0022] S3, adding an alkaline lithium solution to the carboxymethyl cellulose acid colloid solution, and performing an alkalization reaction at 60° C. to 80° C. to obtain a carboxymethyl cellulose lithium colloid solution.

[0023] The present invention uses cheap and readily available sodium carboxymethyl cellulose (CMC-Na) as the initial reactant, adopts acidification under extremely mild reaction conditions to prepare carboxymethyl cellulose acid (CMC-H); and then obtains CMC-Li through alkalization reaction under mild conditions. The specific temperature of the acidification reaction is conducive to improving the solubility of carboxymethyl cellulose, improving the efficiency and substitution degree of the acidification reaction, thereby improving the substitution degree of CMC-Li, and is conducive to improving the first effect and cycle performance of the battery. The specific temperature of the alkalization reaction is conducive to promoting the reaction, improving the substitution degree of CMC-Li, thereby improving the first effect and cycle performance of the battery. Lowering the temperature of the acidification reaction or the alkalization reaction is not conducive to the corresponding reaction, so that the substitution degree of CMC-Li is reduced, and ultimately leads to a decrease in battery performance and an increase in gel risk; increasing the temperature of the acidification reaction or the alkalization reaction is likely to cause hydrochloric acid volatilization, increase the reaction pressure, and high temperature and high pressure are likely to increase side reactions and affect the performance of subsequent products, and the safety risk is increased. The reaction process of the CMC-Li gel of the present invention is mild, the equipment and operation are simple, and no pollution waste is generated, it is environmentally friendly, and the degree of industrialization is high.

[0024] Further preferably, in S1, the mass ratio of the sodium carboxymethyl cellulose to the water is 1:1-1:10, and further preferably 1:3-1:7.

[0025] The present invention can maximize the reactivity of the acidification reaction and improve the degree of substitution by controlling the above mass ratio. If the amount of sodium carboxymethyl cellulose used is too high, it is not conducive to being dissolved in water, and it is not easy to form a stable colloidal solution, which has an adverse effect on the uniformity of subsequent reactions and also causes the subsequent reactions to be incomplete, thereby affecting the overall performance of the battery.

[0026] Further preferably, in S2, the inorganic acid solution is 36wt%~38wt% concentrated hydrochloric acid.

[0027] Further preferably, in S2, the mass ratio of the sodium carboxymethyl cellulose glue to the inorganic acid solution is 1:1-1:6, and further preferably 1:2-1:5.

[0028] Further preferably, in S2, the acidification reaction is carried out under stirring conditions with a linear velocity of 4 m / s to 8 m / s.

[0029] More preferably, in S2, the acidification reaction time is 1 h to 4 h, more preferably 1 h to 3 h.

[0030] Further preferably, in S3, the alkaline lithium-containing solution is a 1 wt% to 30 wt% lithium hydroxide aqueous solution, and the mass concentration is more preferably 5% to 20%.

[0031] Further preferably, in S3, the mass ratio of the carboxymethyl cellulose acid glue solution to the alkaline lithium-containing solution is 1:0.5-1:4, and further preferably 1:0.8-1:2.

[0032] In the present invention, if the concentration of the lithium hydroxide aqueous solution is too low, the reaction is slow, and the amount of solution added is too large, which reduces the solid content of the artificial SEI film glue and affects the coating effect; if the concentration is too high, it is not conducive to the subsequent neutralization reaction and is not conducive to the OH - The rapid reaction stability. Controlling the amount of lithium hydroxide aqueous solution within the above range can ensure that the reaction is under alkaline conditions, and at the same time, control the ratio of organic lithium salt and inorganic lithium salt in the artificial SEI film glue. If the amount of lithium hydroxide aqueous solution added is too low, Li + Replace H + If the amount added is too high, the alkalinity of the carboxymethyl cellulose lithium colloid after the reaction will be too high, resulting in the pH value of the subsequent neutralization reaction being unable to reach below neutral.

[0033] Further preferably, in S3, the alkalization reaction is carried out under stirring conditions at a linear speed of 5 m / s to 15 m / s.

[0034] In steps S2 to S3 of the present invention, the corresponding reaction is carried out under stirring conditions to increase the reaction rate. If the stirring rate is too slow, the contact frequency of the active sites of the reaction is low, which is not conducive to the acidification reaction or the alkalization reaction, resulting in a low reaction degree; since both the acidification reaction and the alkalization reaction are homogeneous reactions, if the stirring rate is too fast, it will cause equipment waste.

[0035] More preferably, in S3, the alkalization reaction time is 1 h to 4 h, more preferably 1 h to 3 h.

[0036] In a second aspect, the present invention provides a method for preparing the artificial SEI film-coated negative electrode material, comprising the following steps:

[0037] The artificial SEI film glue is coated on the surface of the negative electrode material matrix in a spray drying manner to obtain an artificial SEI film coated negative electrode material.

[0038] The method for preparing an artificial SEI film-coated negative electrode material provided by the present invention uses a spray drying method to coat the artificial SEI film glue (liquid phase) on the negative electrode material matrix (solid phase), and the coating is more uniform, the coating effect is excellent, and the uniformity of the coating is improved. It should be noted that the artificial SEI film is formed after the artificial SEI film glue is spray dried.

[0039] In a third aspect, the present invention provides a lithium-ion battery, comprising the artificial SEI film-coated negative electrode material. BRIEF DESCRIPTION OF THE DRAWINGS

[0040] Figure 1 This is a SEM image of the artificial SEI film-coated negative electrode material in Example 1 of the present invention;

[0041] Figure 2 The figure is a comparison chart of cycle curves of the cycle performance test of button batteries made of artificial graphite and the artificial SEI film coated negative electrode material of Example 1 as negative electrode materials at room temperature in the present invention. DETAILED DESCRIPTION

[0042] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.

[0043] The present invention provides a method for preparing an artificial SEI film-coated negative electrode material, which is characterized by comprising the following steps:

[0044] S1, mixing sodium carboxymethyl cellulose with water to obtain sodium carboxymethyl cellulose glue;

[0045] S2, adding concentrated hydrochloric acid to the sodium carboxymethyl cellulose glue solution, performing an acidification reaction at 40° C. to 50° C. to obtain a carboxymethyl cellulose acid glue solution;

[0046] S3, adding a lithium hydroxide aqueous solution to the carboxymethyl cellulose acid colloid solution, and performing an alkalization reaction at 60° C. to 80° C. to obtain a carboxymethyl cellulose lithium colloid solution;

[0047] S4, introducing carbon dioxide and hydrogen fluoride into the carboxymethyl cellulose lithium colloid solution until the pH of the system is 5.5-7.0, thereby obtaining an artificial SEI membrane colloid solution;

[0048] S5, coating the artificial SEI film glue on the surface of the negative electrode material substrate by spray drying to obtain an artificial SEI film coated negative electrode material.

[0049] Example 1

[0050] This embodiment provides an artificial SEI film-coated negative electrode material, which consists of an artificial SEI film and artificial graphite (purchased from Inner Mongolia Xiangfu New Energy Co., Ltd., model RN-P1), and the artificial graphite is coated with the artificial SEI film.

[0051] The method for preparing the above-mentioned artificial SEI film-coated negative electrode material comprises the following steps:

[0052] S1, adding sodium carboxymethyl cellulose and water into a reaction kettle, wherein the mass ratio of sodium carboxymethyl cellulose to the water is 1:5, and mixing them evenly at room temperature to obtain sodium carboxymethyl cellulose glue.

[0053] S2, adding concentrated hydrochloric acid to the reactor, the mass ratio of sodium carboxymethyl cellulose glue and concentrated hydrochloric acid is 1:3, mixing evenly, heating to 40°C, carrying out acidification reaction under stirring conditions with a line speed of 6 m / s, and keeping warm for 1 hour to obtain carboxymethyl cellulose acid glue.

[0054] S3, add 10wt% lithium hydroxide aqueous solution into the reactor, the mass ratio of carboxymethyl cellulose acid colloid solution to lithium hydroxide aqueous solution is 1:1, control the temperature of the reactor to 60°C, carry out alkalization reaction under stirring conditions with an online speed of 8m / s, and keep warm for 1h to obtain carboxymethyl cellulose lithium colloid solution.

[0055] S4, introducing carbon dioxide and hydrogen fluoride into the reactor for neutralization reaction, the molar ratio of carbon dioxide to hydrogen fluoride is 1:1, until the pH of the reaction system is 7.0, the reaction is completed, and an artificial SEI membrane glue solution is obtained.

[0056] S5, using a spray drying method to uniformly coat the artificial SEI membrane glue on the surface of the artificial graphite, the mass ratio of the artificial SEI membrane glue to the artificial graphite is 2:100, and an artificial SEI membrane coated negative electrode material is obtained.

[0057] The artificial SEI film coated negative electrode material prepared in this embodiment was scanned by electron microscope, and the scanning results are as follows: Figure 1 It can be seen that the coating effect of the artificial SEI film-coated negative electrode material is better, and there is no impact on the product appearance and microscopic morphology; and the processing performance of the negative electrode material can be improved by relying on the characteristics of the artificial SEI film glue.

[0058] Example 2

[0059] This embodiment provides an artificial SEI film-coated negative electrode material, which consists of an artificial SEI film and natural graphite (purchased from Dalian Hongguang Lithium Industry Co., Ltd., model HG-X2), and the natural graphite is coated with the artificial SEI film.

[0060] The method for preparing the above-mentioned artificial SEI film-coated negative electrode material comprises the following steps:

[0061] S1, adding sodium carboxymethyl cellulose and water into a reaction kettle, wherein the mass ratio of sodium carboxymethyl cellulose to the water is 1:3, and mixing them evenly at room temperature to obtain sodium carboxymethyl cellulose glue.

[0062] S2, add concentrated hydrochloric acid to the reactor, the mass ratio of sodium carboxymethyl cellulose glue and concentrated hydrochloric acid is 1:2, mix well, heat to 45°C, carry out acidification reaction under stirring conditions with a line speed of 4m / s, keep warm for 2h, and obtain carboxymethyl cellulose acid glue.

[0063] S3, add 5wt% lithium hydroxide aqueous solution into the reactor, the mass ratio of carboxymethyl cellulose acid colloid solution to lithium hydroxide aqueous solution is 1:2.5, control the temperature of the reactor to 70°C, carry out alkalization reaction under stirring conditions with an online speed of 10m / s, keep warm for 1.5h, and obtain carboxymethyl cellulose lithium colloid solution.

[0064] S4, introducing carbon dioxide and hydrogen fluoride into the reactor for neutralization reaction, the molar ratio of carbon dioxide to hydrogen fluoride is 0.9:1, until the pH of the reaction system is 6.5, the reaction is completed, and an artificial SEI membrane glue solution is obtained.

[0065] S5, using a spray drying method to evenly wrap the artificial SEI membrane glue on the surface of natural graphite, the mass ratio of the artificial SEI membrane glue to the natural graphite is 3:100, and an artificial SEI membrane-coated negative electrode material is obtained.

[0066] Example 3

[0067] This embodiment provides an artificial SEI film-coated negative electrode material, which consists of an artificial SEI film and hard carbon (purchased from Kuraray Co., Ltd. of Japan, model No. 2), and the hard carbon is coated by the artificial SEI film.

[0068] The method for preparing the above-mentioned artificial SEI film-coated negative electrode material comprises the following steps:

[0069] S1, adding sodium carboxymethyl cellulose and water into a reaction kettle, wherein the mass ratio of sodium carboxymethyl cellulose to the water is 1:7, and mixing them evenly at room temperature to obtain sodium carboxymethyl cellulose glue.

[0070] S2, add concentrated hydrochloric acid to the reactor, the mass ratio of sodium carboxymethyl cellulose glue and concentrated hydrochloric acid is 1:4, mix well, heat to 50°C, carry out acidification reaction under stirring conditions with a line speed of 8m / s, keep warm for 1.5h, and obtain carboxymethyl cellulose acid glue.

[0071] S3, add 20wt% lithium hydroxide aqueous solution into the reactor, the mass ratio of carboxymethyl cellulose acid colloid solution to lithium hydroxide aqueous solution is 1:0.7, control the temperature of the reactor to 80°C, carry out alkalization reaction under stirring conditions with an online speed of 5m / s, and keep warm for 1h to obtain carboxymethyl cellulose lithium colloid solution.

[0072] S4, introducing carbon dioxide and hydrogen fluoride into the reactor for neutralization reaction, the molar ratio of carbon dioxide to hydrogen fluoride is 1.1:1, until the pH of the reaction system is 6.0, the reaction is completed, and an artificial SEI membrane glue solution is obtained.

[0073] S5, using a spray drying method to uniformly coat the artificial SEI membrane glue on the surface of the hard carbon, the mass ratio of the artificial SEI membrane glue to the hard carbon is 5:100, and an artificial SEI membrane coated negative electrode material is obtained.

[0074] Example 4

[0075] This embodiment provides an artificial SEI film-coated negative electrode material, which consists of an artificial SEI film and soft carbon (purchased from BCT New Materials Group Co., Ltd., model BSC-3), and the soft carbon is coated with the artificial SEI film.

[0076] The method for preparing the above-mentioned artificial SEI film-coated negative electrode material comprises the following steps:

[0077] S1, adding sodium carboxymethyl cellulose and water into a reaction kettle, wherein the mass ratio of sodium carboxymethyl cellulose to the water is 1:1.5, and mixing them evenly at room temperature to obtain sodium carboxymethyl cellulose glue.

[0078] S2, adding concentrated hydrochloric acid to the reactor, the mass ratio of sodium carboxymethyl cellulose glue and concentrated hydrochloric acid is 1:1, mixing evenly, heating to 40°C, carrying out acidification reaction under stirring conditions with a line speed of 5m / s, and keeping warm for 3h to obtain carboxymethyl cellulose acid glue.

[0079] S3, add 25wt% lithium hydroxide aqueous solution into the reactor, the mass ratio of carboxymethyl cellulose acid colloid solution to lithium hydroxide aqueous solution is 1:3.5, control the temperature of the reactor to 70°C, carry out alkalization reaction under stirring conditions with an online speed of 15m / s, keep warm for 2.5h, and obtain carboxymethyl cellulose lithium colloid solution.

[0080] S4, introducing carbon dioxide and hydrogen fluoride into the reactor for neutralization reaction, the molar ratio of carbon dioxide to hydrogen fluoride is 1.2:1, until the pH of the reaction system is 5.5, the reaction is completed, and an artificial SEI membrane glue solution is obtained.

[0081] S5, using a spray drying method to uniformly coat the artificial SEI membrane glue on the surface of the soft carbon, the mass ratio of the artificial SEI membrane glue to the soft carbon is 0.8:100, and an artificial SEI membrane coated negative electrode material is obtained.

[0082] Example 5

[0083] This embodiment provides an artificial SEI film-coated negative electrode material, which consists of an artificial SEI film and silicon carbon (purchased from Lanxi Zhide New Energy Materials Co., Ltd., model S0310), and the silicon carbon is coated with the artificial SEI film.

[0084] The method for preparing the above-mentioned artificial SEI film-coated negative electrode material comprises the following steps:

[0085] S1, adding sodium carboxymethyl cellulose and water into a reaction kettle, wherein the mass ratio of sodium carboxymethyl cellulose to the water is 1:9, and mixing them evenly at room temperature to obtain sodium carboxymethyl cellulose glue.

[0086] S2, add concentrated hydrochloric acid to the reactor, the mass ratio of sodium carboxymethyl cellulose glue and concentrated hydrochloric acid is 1:6, mix well, heat to 50°C, carry out acidification reaction under stirring conditions with a line speed of 7m / s, keep warm for 2h, and obtain carboxymethyl cellulose acid glue.

[0087] S3, add 2wt% lithium hydroxide aqueous solution into the reactor, the mass ratio of carboxymethyl cellulose acid colloid solution to lithium hydroxide aqueous solution is 1:0.5, control the temperature of the reactor to 70°C, carry out alkalization reaction under stirring conditions with an online speed of 10m / s, and keep warm for 3h to obtain carboxymethyl cellulose lithium colloid solution.

[0088] S4, introducing carbon dioxide and hydrogen fluoride into the reactor for neutralization reaction, the molar ratio of carbon dioxide to hydrogen fluoride is 0.8:1, until the pH of the reaction system is 7.0, the reaction is completed, and an artificial SEI membrane glue solution is obtained.

[0089] S5, using a spray drying method to uniformly coat the artificial SEI membrane glue on the surface of silicon carbon, the mass ratio of the artificial SEI membrane glue to silicon carbon is 10:100, and an artificial SEI membrane coated negative electrode material is obtained.

[0090] Example 6

[0091] This embodiment provides a method for preparing an artificial SEI film-coated negative electrode material, which is similar to that of Embodiment 1, except that in S3, the alkalization temperature is replaced with 45° C. The remaining conditions are the same as those of Embodiment 1 and will not be described in detail.

[0092] Example 7

[0093] This embodiment provides a method for preparing an artificial SEI film-coated negative electrode material, which is similar to that of Embodiment 1, except that: in S1, water is replaced with an ethanol aqueous solution of equal mass (the mass ratio of ethanol to water is 1:1). The remaining conditions are the same as those of Embodiment 1 and will not be described in detail.

[0094] Comparative Example 1

[0095] This comparative example provides a method for preparing an artificial SEI film-coated negative electrode material (without the introduction of carbon dioxide and hydrogen fluoride), comprising the following steps:

[0096] S1~S3 are the same as those in Example 1 and will not be described in detail.

[0097] S4, washing the carboxymethyl cellulose lithium gel solution with water until it is neutral, and concentrating it to obtain an artificial SEI membrane gel solution.

[0098] S5 is the same as in Example 1 and will not be described in detail.

[0099] Comparative Example 2

[0100] This comparative example provides an amorphous carbon-coated negative electrode material, which is composed of asphalt (purchased from Liaoning Xinde New Materials Technology Co., Ltd., model 200#, softening point 200°C) and artificial graphite (purchased from Inner Mongolia Xiangfu New Energy Co., Ltd., model RN-P1), and the artificial graphite is coated with asphalt.

[0101] The method for preparing the above-mentioned amorphous carbon-coated negative electrode material comprises the following steps:

[0102] S1. Grind the asphalt to 2 μm~6 μm by jet mill, add artificial graphite, the mass ratio of asphalt to artificial graphite is 3:100, put it into VC mixer and stir at 30 rpm for 30 min to obtain a mixed material.

[0103] S2, the mixed material is loaded into a crucible, and under the protection of nitrogen, high-temperature carbonization is carried out in a track kiln at 1150°C. After keeping the temperature for 8 hours, the mixture is crushed and sieved to obtain an amorphous carbon-coated negative electrode material.

[0104] Electrochemical performance test

[0105] In order to verify the electrochemical properties of the artificial SEI film-coated negative electrode material provided by the present invention, the artificial SEI film-coated negative electrode material provided by Examples 1 to 7 of the present invention, the artificial SEI film-coated negative electrode material provided by Comparative Example 1, the amorphous carbon-coated negative electrode material provided by Comparative Example 2, and unmodified artificial graphite, natural graphite, hard carbon, soft carbon and silicon-carbon negative electrode materials were prepared into lithium battery button cells, and the gram capacity, first coulomb efficiency, cell rate and cycle performance of the lithium battery button cells were tested (the recording condition was once per minute).

[0106] Preparation of lithium battery button cell: The negative electrode material, aqueous binder (styrene butadiene rubber SBR) and conductive agent (carbon black SP) were mixed at a mass ratio of 90:7:3, and the resulting mixture was applied to copper foil with a coating density of 10 mg / cm 2 Then it is dried at 90℃~110℃ and rolled to a compacted density of 1.3g / cm 3, cut into discs as negative electrodes; select metal lithium sheets as counter electrodes, and 13μm thick PE materials as separators (porosity is about 48%); the electrolyte consists of solvents, additives and lithium salt LiPF6, the solvent is ethylene carbonate (EC) and propylene carbonate in a mass ratio of 1:1, the additive is fluoroacetate (FEC) accounting for 5% of the solvent mass, and the concentration of LiPF6 in the electrolyte is 1.0mol·L -1 The total amount of electrolyte added is 0.1 mL, and a button battery of model CR2032 is assembled.

[0107] The detection process of gram capacity and first coulombic efficiency is shown in Table 1. The discharge capacity and charge capacity of this process are recorded, and the mass of active material on the negative electrode sheet is calculated, thereby calculating its charge-discharge specific capacity and first charge-discharge efficiency. The test results are shown in Table 4.

[0108] m 活性物质 =(m 负极极片 -m 铜箔 )×active substance%;

[0109] Discharge capacity in grams = C 放电 / m 活性物质 ;

[0110] Charge capacity in grams = C 充电 / m 活性物质 ;

[0111] First discharge efficiency = charging gram capacity / discharging gram capacity × 100%.

[0112] Table 1 Detection process of gram capacity and first coulombic efficiency

[0113]

[0114] The detection process of fast charging of the battery cell is shown in Table 2. The discharge capacity and charge capacity of this process are recorded, and the mass of the active material on the negative electrode plate is calculated, thereby calculating its charge and discharge specific capacity. The test results are shown in Table 4.

[0115] Table 2 Battery fast charging detection process

[0116]

[0117] The test process of the cycle performance is shown in Table 3. The discharge capacity and charge capacity of this process are recorded, and the cycle retention rate is calculated. The test results are shown in Table 4. Figure 2A comparison chart of cycle curves of button batteries made of artificial graphite and the artificial SEI film-coated negative electrode material of Example 1 as negative electrode materials, respectively, during a cycle performance test (0.5C / 0.5C) at room temperature is given, wherein "0.5C / 0.5C" means that the cycle test is completed under the conditions of charging at a 0.5C rate and discharging at a 0.5C rate.

[0118] Cycle retention rate = charging capacity of step 10 in the 500th cycle / charging capacity of step 10 in the 1st cycle.

[0119] Table 3 Cycle performance test process

[0120]

[0121] Table 4 Electrochemical performance test results of button cells made with different negative electrode materials

[0122]

[0123] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modification, equivalent substitution or improvement made within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. An artificial SEI film-coated negative electrode material, characterized in that: It includes a negative electrode material matrix and an artificial SEI film coated on the surface of the negative electrode material matrix; The raw material of the artificial SEI film is an artificial SEI film glue, and the preparation method of the artificial SEI film glue comprises the following steps: S1, mixing sodium carboxymethyl cellulose with water to obtain sodium carboxymethyl cellulose glue; S2, adding an inorganic acid solution to the sodium carboxymethyl cellulose glue solution, and performing an acidification reaction at 40° C. to 50° C. to obtain a carboxymethyl cellulose acid glue solution; S3, adding an alkaline lithium-containing solution to the carboxymethyl cellulose acid colloid solution, and performing an alkalization reaction at 60° C. to 80° C. to obtain a carboxymethyl cellulose lithium colloid solution; S4, introducing carbon dioxide and hydrogen fluoride into the carboxymethyl cellulose lithium colloid solution until the pH value of the system is 5.5-7.0, thereby obtaining an artificial SEI membrane colloid solution.

2. The artificial SEI film-coated negative electrode material according to claim 1, characterized in that: The mass ratio of the artificial SEI film glue to the negative electrode material matrix is ​​(0.5~10):

100.

3. The artificial SEI film-coated negative electrode material according to claim 1 or 2, characterized in that: The negative electrode material matrix is ​​selected from at least one of artificial graphite and natural graphite; or The negative electrode material matrix is ​​selected from at least one of hard carbon, soft carbon, silicon carbon or silicon oxygen.

4. The artificial SEI film-coated negative electrode material according to claim 1, characterized in that: In S4, the molar ratio of the carbon dioxide to the hydrogen fluoride is 0.8:1 to 1.2:

1.

5. The artificial SEI film-coated negative electrode material according to claim 1, characterized in that: In S1, the mass ratio of the sodium carboxymethyl cellulose to the water is 1:1 to 1:10; In S2, the inorganic acid solution is concentrated hydrochloric acid; In S2, the mass ratio of the sodium carboxymethyl cellulose glue and the inorganic acid solution is 1:1 to 1:

6.

6. The artificial SEI film-coated negative electrode material according to claim 1, characterized in that: In S3, the alkaline lithium-containing solution is a 1wt% to 30wt% lithium hydroxide aqueous solution; In S3, the mass ratio of the carboxymethyl cellulose acid gel solution to the alkaline lithium-containing solution is 1:0.5-1:

4.

7. The artificial SEI film-coated negative electrode material according to claim 1, characterized in that: In S2, the acidification reaction is carried out under stirring conditions at a linear speed of 4 m / s to 8 m / s; In S2, the acidification reaction time is 1h~4h; In S3, the alkalization reaction is carried out under stirring conditions at a linear speed of 5 m / s to 15 m / s; In S3, the alkalization reaction time is 1h~4h.

8. The method for preparing the artificial SEI film-coated negative electrode material according to any one of claims 1 to 7, characterized in that: The following steps are involved: The artificial SEI film glue is coated on the surface of the negative electrode material substrate in a spray drying manner to obtain an artificial SEI film coated negative electrode material.

9. A lithium ion battery, characterized in that: It comprises the artificial SEI film-coated negative electrode material according to any one of claims 1 to 7 or the artificial SEI film-coated negative electrode material prepared by the preparation method of the artificial SEI film-coated negative electrode material according to claim 8.

Citation Information

Patent Citations

  • Artificial SEI film protection lithium negative electrode for lithium primary battery and preparation method of artificial SEI film protection lithium negative electrode

    CN116454282A

  • Negative electrode material and preparation method and application thereof

    CN117550587A